2014
DOI: 10.2147/ppa.s46667
|View full text |Cite
|
Sign up to set email alerts
|

Bromfenac ophthalmic solution for the treatment of postoperative ocular pain and inflammation: safety, efficacy, and patient adherence

Abstract: Ophthalmic nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used by clinicians to manage ocular inflammation and pain following cataract surgery. Over the past decade, the US Food and Drug Administration has approved multiple topical NSAIDs for these purposes, including several reformulated products. One of these medications, bromfenac ophthalmic solution, has a long and extensive history, with proven efficacy and safety in patients following cataract surgery. The evolution of bromfenac ophthalmic so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
3
12
0
2
Order By: Relevance
“…In particular, our study used bromfenac 0.075% encased in DuraSite, and our efficacy results were similar to others published on bromfenac 0.07% without DuraSite 16,17. However, the bromfenac 0.075% in this trial was able to prevent pain, which has not been established with other formulations of bromfenac.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In particular, our study used bromfenac 0.075% encased in DuraSite, and our efficacy results were similar to others published on bromfenac 0.07% without DuraSite 16,17. However, the bromfenac 0.075% in this trial was able to prevent pain, which has not been established with other formulations of bromfenac.…”
Section: Discussionsupporting
confidence: 86%
“…Our results add to the recent literature about the analgesic effects of bromfenac postcataract surgery 1417. In particular, our study used bromfenac 0.075% encased in DuraSite, and our efficacy results were similar to others published on bromfenac 0.07% without DuraSite 16,17.…”
Section: Discussionsupporting
confidence: 86%
“…Postoperative inflammation and pain following cataract surgery are routinely managed with topical ophthalmic corticosteroids and/or nonsteroidal anti-inflammatory drugs (NSAIDs) [2,3]. In order to be clinically effective, topical ophthalmic NSAIDs must be capable of penetrating the affected tissues and remaining within those tissues at sufficient levels throughout the dosing interval [3].…”
Section: Introductionmentioning
confidence: 99%
“…The NSAID bromfenac has previously been formulated as a 0.09 % ophthalmic solution (hereafter referred to as bromfenac 0.09 %) with a pH of 8.3 [6]. A formulation of bromfenac with a pH of 7.8 has recently been developed, permitting a reduction in the concentration of the active ingredient to 0.07 % [3]. This article reviews pharmacological, therapeutic efficacy and tolerability data relevant to the use of bromfenac ophthalmic solution 0.07 % (hereafter referred to as bromfenac 0.07 %) [Prolensa Ò ; Bausch & Lomb Inc.] for the management of postoperative inflammation and pain following cataract surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed a significant anti-inflammatory response to bromfenac and they recommended using the drug instead of topical steroids following cataract surgery. Other studies have shown that bromfenac is a favourable drug and a valuable addition to the NSAID armamentarium for the management of CMO [11][12][13].…”
Section: Discussionmentioning
confidence: 99%